Management of Prosthetic Joint Infection - Tande, Aaron J; Gomez-Urena, Eric O; Berbari, Elie F; Osmon, Douglas R (Infectious disease clinics of North America, 2017)
Although uncommon, prosthetic joint infection is a devastating complication. This challenging condition requires a coordinated management approach to achieve good patient outcomes. This review details the general principles to consider when managing patients with prosthetic joint infection. The different medical/surgical treatment strategies and how to appropriately select a strategy are discussed. The data to support each strategy are presented, along with discussion of antimicrobial strategies in specific situations.